Evidence that C/EBP-β LAP Increases Fat Metabolism and Protects Against Diet-Induced Obesity in Response to mTOR Inhibition - Bitto, Alessandro; Tatom, Nicole; Krivak, Thomas; Grotz, Peter; Kaeberlein, Matt (Frontiers in Aging, 2021)
Aging and obesity are common risk factors for numerous chronic pathologies, and the compounding effects of old age and increased adiposity pose a serious threat to public health. Starting from the assumption that aging and obesity may have shared underpinnings, we investigated the antiobesogenic potential of a successful longevity intervention, the mTORC1 inhibitor rapamycin. We find that rapamycin prevents diet-induced obesity in mice and increases the activity of C/EBP-β LAP, a transcription factor that regulates the metabolic shift to lipid catabolism observed in response to calorie restriction. Independent activation of C/EBP-β LAP with the antiretroviral drug adefovir dipivoxil recapitulates the anti-obesogenic effects of rapamycin without reducing signaling through mTORC1 and increases markers of fat catabolism in the liver. Our findings support a model that C/EBP-β LAP acts downstream of mTORC1 signaling to regulate fat metabolism and identifies a novel drug that may be exploited to treat obesity and decrease the incidence of age-related disease.